Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/nar/gkx546
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic delivery of siRNA by ultra-high affinity dsRNA binding proteins

Abstract: Protein-based methods of siRNA delivery are capable of uniquely specific targeting, but are limited by technical challenges such as low potency or poor biophysical properties. Here, we engineered a series of ultra-high affinity siRNA binders based on the viral protein p19 and developed them into siRNA carriers targeted to the epidermal growth factor receptor (EGFR). Combined in trans with a previously described endosome-disrupting agent composed of the pore-forming protein Perfringolysin O (PFO), potent silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
0
15
1
Order By: Relevance
“…Previous cytosolic siRNA dose-response estimates have provided data at single time-points without information on cell-to-cell variability 19 . Cytosolic IC50 was estimated to ~2000-4000 molecules using electron microscopy of gold-labelled siRNA 9 and through Ago2-immuno precipitation, IC50 was determined to be 10-110 RISC-loaded siRNA molecules (but with unclear RISC-loading efficiencies) 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous cytosolic siRNA dose-response estimates have provided data at single time-points without information on cell-to-cell variability 19 . Cytosolic IC50 was estimated to ~2000-4000 molecules using electron microscopy of gold-labelled siRNA 9 and through Ago2-immuno precipitation, IC50 was determined to be 10-110 RISC-loaded siRNA molecules (but with unclear RISC-loading efficiencies) 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of noncovalent protein-based RNAi delivery, affinity of the carrier for the RNA is an important factor for stability in circulation (and intracellularly), and scientists have sought to enhance delivery efficiency by enhancing affinity. For example, Yang et al enhanced the binding affinity of p19 for dsRNA through yeast display to a dissociation constant ( k d ) of 11 pM [75]. Contrast this with the reported affinity of ~ 72 nM for Ago2 and ssRNA, and it remains unclear why Ago2 would retain stability in circulation and other constructs would not [128].…”
Section: Discussionmentioning
confidence: 99%
“…Danielson et al fused a cell-penetrating Tat peptide to p19 dimers, and saw substantial knockdown in vitro only when co-treated with cell-penetrating endosomolytic compound E5-TAT [74]. Yang et al performed yeast-display directed evolution on p19, ultimately finding a double mutant with 160-fold greater binding affinity [75]. The p19 monomers were then fused to an EGFR-targeting domain and added to cells in vitro, along with an EGFR-targeting endosomolytic compound.…”
Section: Engineering Of Protein-mediated Rna Deliverymentioning
confidence: 99%
“…To achieve an efficient intracellular siRNA delivery, the binding between the protein and the nucleotide has to be strong enough to protect the cargo, but it also has to be disrupted in the last step of the delivery process. A systematic study using high-affinity dsRNA binding proteins, derived from p19 of Carnation Italian Ringspot Virus¸ showed that, even for dissociation constants in the low pM range, the inhibitory binding-limit was not reached 78 . However, to achieve cytosolic delivery of the siRNA in this study a second pore forming Perfringolysin O protein was required to achieve endosomal escape 78 .…”
Section: Protein Basedmentioning
confidence: 99%
“…These results indicate that a reversible bond is not a prerequisite for activity 83 , as the linker is at the sense strand and it might not affect the antisense strand loading into the RISC complex. However, in all these examples of protein mediated delivery, the endosomal escape is usually the limiting factor and the addition of endosomolytic agents as pore forming toxins 78 or CPPs 77 is sometimes required to achieve efficient cargo delivery.…”
Section: Protein Basedmentioning
confidence: 99%